Micropropagation of Vaccinium meridionale Sw.: interaction between basal media and cytokinins, physiological quality of shoots, and ex vitro rooting - Huaman, Eyner (2025)
Vaccinium meridionale is an Andean species of high nutraceutical value whose conventional propagation is limited by its low multiplication rate. In this study, an integrated micropropagation protocol was developed, encompassing in vitro establishment through ex vitro rooting. During the establishment phase, fungal contaminants were identified, detecting genera such as Diaporthe, Fusarium, Colletotrichum and Phoma. In the multiplication phase, the basal media Driver and Kuniyuki (DKW), Woody Plant Medium (WPM) and Murashige and Skoog (MS) were evaluated, supplemented with zeatin (Zea), 2-isopentenyladenine (2iP), meta-topolin (mT) and thidiazuron (TDZ), all applied at equimolar concentrations of 2.5 μM. Morphogenic parameters, photosynthetic pigment content, SPAD index and elemental composition of regenerated tissues were quantified. DKW medium supplemented with Zea or 2iP promoted the formation of 9–10 shoots, with lengths of 2.5–2.9 cm, SPAD values of 35–36, and chlorophyll content >31 μg/mL. The accumulation of P, Ca, Mg, Fe, Zn, Cu and Mn in the tissues varied widely among treatments. During rooting, the application of 500 ppm naphthaleneacetic acid (NAA) induced the formation of longer roots, as well as vigorous and elongated shoots with a high number of leaves. This optimized protocol provides a valuable tool for the propagation of V. meridionale, with potential applications in conservation, genetic improvement and commercial plant production.